DATA STRUCTURE OF MEDICAL INFORMATION ORGANIZATION AND SELECTING OPTIMAL PATIENT TREATMENT STRATEGIES - Davydko, Oleksandr; Levchyk, Liliia; Khlimenkov, Olexiy; Averianova, Olga (Proceedings of National Aviation University, 2021)
Purpose: The purpose of this article is to develop a clinical information storage and medical decision support system for daily use by physicians during their work with patients. Methods: The article considered approaches to achieve the research goal through the creation of a backend on Django Rest Framework, as well as the application of the simplex method to perform treatment optimization. Results: A server-side software product was obtained, where a special database was implemented, which takes into account the requirements for the data structure of the organization of medical information, and a module for selecting optimal treatment strategies for patients was created. Discussion: The conducted research allowed us to obtain a prototype of medical information system, which will be useful due to its versatility in the data structure of the organization of medical data and the use of machine learning methods to optimize treatment strategies.